ANALISIS PELAYANAN ADMINISTRASI DI KELURAHAN BANGGAE KABUPATEN MAJENE (STUDI KASUS PEMBUATAN SURAT KETERANGAN TIDAK MAMPU DAN SURAT AHLI WARIS) - Sjuaib Hannan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2016)
This study aims to determine the correspondence services and factors that influence mailing services in the Banggae village of Majene Regency. The approach used is descriptive qualitative. The technique of data collection is done by library research, field research consisting of, observation and interviews. The results of the study show that the public services in the manufacture of non-capable certificates and letters of heirs at the Banggae Urban Village Office can be said to have materialized well. This can be seen from the indicators in public services, namely, service procedures, service requirements, service time, service costs, service products, facilities / infrastructure and competency of service providers. where all these indicators are in good category. Employee performance in making Non-Capable Certificates and Letters of Heirs has been implemented so far. This can be seen from the other existing indicators: quality and quantity of performance, employee reliability and employee work attitudes. Obstacles that were encountered were, among others, a lack of public awareness about the importance of administrative completeness in the process of making this inadequate Certificate and Letter of Heirs.